An intensive winter fixture schedule induces a transient fall in salivary IgA in English Premier League soccer players - Morgans, R.; Orme, P.; Aderson, L.; Drust, B.; Morton, J. P. (Research in Sports Medicine, 2014)
We examined the effects of an intensive fixture schedule on salivary IgA (SIgA) concentration in professional soccer players from the English Premier League. Salivary samples were obtained from 21 males who participated in seven games over a 30-day period during December 2013 and January 2014 (games 1-5 occurred in a 15-day period). Salivary-IgA decreased (P < 0.05) at 2 days post-game 3 (45 ± 9 µg mL-1), 4 (52 ± µg mL-1) and 5 (41 ± 10 µg mL-1) compared with game 1 (139 ± 25 µg mL-1). When the normal fixture schedule resumed (i.e. one game per week), SIgA returned towards baseline such that game 6 and 7 values were not different (P > 0.05) from game 1 (91 ± 18 and 99 ± 21 µg mL-1, respectively). Data demonstrate for the first time that a congested winter fixture schedule induces detectable perturbations to mucosal immunity in professional soccer players.